Surveillance for adverse events following use of live attenuated chikungunya vaccine, United States, 2024, and the associated public health response in 2024 and 2025 - J Erin Staples (Eurosurveillance)
A live attenuated chikungunya vaccine (IXCHIQ) received licensure in the United States (US) for ≥ 18-year-olds in November 2023. Post-licensure safety surveillance identified 28 adverse events in 2024 among US persons, including six neurological or cardiac serious adverse events (SAEs) in males ≥ 65 years. In early 2025, providers were alerted, a precaution for older persons was issued and vaccine guidance was updated. In May, following 11 additional SAEs reported outside the US, use in older persons was temporarily paused until 6 August 2025.